Digitalisation and quality management: problems and prospects. Issue 12 (10th September 2021) - Elg, Mattias; Birch-Jensen, Andrea; Gremyr, Ida; Martin, Jason; Melin, Ulf
Abstract: Digitalisation provides both challenges and opportunities for Quality Management (QM). The purpose of this study is to identify various roles QM practitioners play in digitalisation initiatives to uncover the challenges and potential of QM's digitalisation journey. This issue is addressed through an analytical framework that stresses two dimensions: the exploration and exploitation of digitalised QM processes and value creation, which is performed by the customer or in interactions facilitated by the provider. Through a multiple-case study of four large Swedish organisations, we propose six different challenges and corresponding roles for QM. Further, the study identifies challenges of digitalisation affecting both exploitative and explorative practices throughout an organisation's value creation process. This research contributes to the existing literature with empirical evidence on the challenges induced by digitalisation, an area often discussed but not as often studied empirically.